2016
DOI: 10.1159/000452764
|View full text |Cite
|
Sign up to set email alerts
|

Anti-KIR4.1 Antibodies in Chinese Patients with Central Nervous System Inflammatory Demyelinating Disorders

Abstract: Objectives: The aim of this study was to explore the frequency of KIR4.1 antibodies in patients with multiple sclerosis (MS) and in control groups using a cell-based assay. Materials and Methods: A transfected HEK-293A cell line expressing KIR4.1 was established to test for the presence of KIR4.1 antibodies in blood serum. We tested 904 subjects, including 188 patients with MS, 264 patients with neuromyelitis optica spectrum disorders (NMOSD), 209 patients with other inflammatory neurologic disease (OIND), 203… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Some studies have suggested, in opposite to the outlined hypocretin-neuron-specific degeneration for NT1, a broader immune reactivity against other areas of the brain [26,27]. Here, we test the autoantibody reactivity for NT1 patients against multiple sclerosis, as another HLA-DQB1 Ã 06:02-related neurological disorder, associated autoantigens ATP-dependent Inwardly Rectifying Potassium Channel (KIR4.1) [28][29][30][31][32][33][34][35][36] and calcium-activated chloride channel Anoctamin 2 (ANO2) [37].…”
Section: Introductionmentioning
confidence: 92%
“…Some studies have suggested, in opposite to the outlined hypocretin-neuron-specific degeneration for NT1, a broader immune reactivity against other areas of the brain [26,27]. Here, we test the autoantibody reactivity for NT1 patients against multiple sclerosis, as another HLA-DQB1 Ã 06:02-related neurological disorder, associated autoantigens ATP-dependent Inwardly Rectifying Potassium Channel (KIR4.1) [28][29][30][31][32][33][34][35][36] and calcium-activated chloride channel Anoctamin 2 (ANO2) [37].…”
Section: Introductionmentioning
confidence: 92%
“…In 2012, Srivastava et al screened serum samples aiming to identify CNS-specific antibodies in MS, and identified the glial potassium channel Kir4.1 as one of the serum immune targets in patients with MS. As aforementioned, antibodies against KIR4.1 were observed in 46.9% of the patients with MS, but were essentially absent in those with OND and HCs [14]. However, subsequent studies revealed controversial results, and were unable to confirm the value of KIR4.1 antibodies for an MS diagnosis [41][42][43][44][45][46][47][48][49][50][51]. We reviewed and summarized the prevalence of anti-Kir4.1 antibodies in patients with MS in 13 previous studies (Table 2).…”
Section: Anti-kir41 Antibodies In Ms: Specificitymentioning
confidence: 99%
“…These studies included 12 in adult patients and one in children. The studies were developed in the USA (3) [41][42][43], China (1) [44], France (1) [45], Germany (2) [14,40], Israel (1) [46], Italy (2) [47,48], Japan (2) [49,50], and Spain (1) [51]. Watanabe et al measured the anti-Kir4.1 antibodies by an enzyme-linked immunosorbent assay (ELISA) using a synthetic Kir4.1 83-120 peptide [49].…”
Section: Anti-kir41 Antibodies In Ms: Specificitymentioning
confidence: 99%
See 2 more Smart Citations